The ordinary princess - Kaye, M. M; Ibrahim, Heba (Cairo ibda3, 2024)
Along with wit, charm, and courage, princess amy of phantasmorania receives a special fairy christening ordinariness. unlike her sex beautiful sisters, she has brown hair and freckles, and would rather have adventures than play the harp, embroider tapestries ... or become a queen. when her royal parents try to marry her off, Amy runs away and, because she's so ordinary, easily becomes the fourteenth assistant kitchen maid at a neighboring palace, and there ... much to everyone's surprise ... she meets a prince just as ordinary (and special) as she is!
English stories
Keywords: English stories